Ca2+ Cycling Impairment in Heart Failure Is Exacerbated by Fibrosis: Insights Gained From Mechanistic Simulations - Mora, Maria T.; Ferrero, Jose M.; Gomez, Juan F.; Sobie, Eric A.; Trenor, Beatriz (Frontiers in Physiology, 2018)
Heart failure (HF) is characterized by altered Ca2+ cycling, resulting in cardiac contractile dysfunction. Failing myocytes undergo electrophysiological remodeling, which is known to be the main cause of abnormal Ca2+ homeostasis. However, structural remodeling, specifically proliferating fibroblasts coupled to myocytes in the failing heart, could also contribute to Ca2+ cycling impairment. The goal of the present study was to systematically analyze the mechanisms by which myocyte-fibroblast coupling could affect Ca2+ dynamics in normal conditions and in HF. Simulations of healthy and failing human myocytes were performed using established mathematical models, and cells were either isolated or coupled to fibroblasts. Univariate and multivariate sensitivity analyses were performed to quantify effects of ion transport pathways on biomarkers computed from intracellular [Ca2+] waveforms. Variability in ion channels and pumps was imposed and populations of models were analyzed to determine effects on Ca2+ dynamics. Our results suggest that both univariate and multivariate sensitivity analyses are valuable methodologies to shed light into the ionic mechanisms underlying Ca2+ impairment in HF, although differences between the two methodologies are observed at high parameter variability. These can result from either the fact that multivariate analyses take into account ion channels or non-linear effects of ion transport pathways on Ca2+ dynamics. Coupling either healthy or failing myocytes to fibroblasts decreased Ca2+ transients due to an indirect sink effect on action potential and thus on Ca2+ related currents. Simulations that investigated restoration of normal physiology in failing myocytes showed that Ca2+ cycling can be normalized by increasing SERCA and L-type Ca2+ current activity while decreasing Na+-Ca2+ exchange and SR Ca2+ leak. Changes required to normalize action potentials in failing myocytes depended on whether myocytes were coupled to fibroblasts. In conclusion, univariate and multivariate sensitivity analyses are helpful tools to understand how Ca2+ cycling is impaired in heart failure and how this can be exacerbated by coupling of myocytes to fibroblasts. The design of pharmacological actions to restore normal activity should take into account the degree of fibrosis in the failing heart.